ANALISIS KINERJA KARYAWAN DENGAN MENGGUNAKAN PERFORMANCE ANALYSIS QUADRANT (PAQ) PADA PT. BANK NEGARA INDONESIA (PERSERO) Tbk KANTOR CABANG MAUMERE - Cindy Claudia Kana Talo; Imanuel Wellem; Viktor Eko Transilvanus (Jurnal Projemen UNIPA, 2026)
This study aims to analyze employee performance and identify factors that need to be considered in efforts to improve employee performance at PT. Bank Negara Indonesia (Persero) Tbk Maumere Branch Office using the Performance Analysis Quadrant (PAQ) method. Data were collected through interviews and questionnaires. Interviews were used to obtain an overview of employee performance which was analyzed descriptively qualitatively, while questionnaires were used to measure aspects of employee knowledge and work attitudes which were then analyzed using PAQ. The results of the study indicate that in general employee performance is in the good category and has been in accordance with the company's operational standards, however there are still obstacles in the aspects of work quality and timeliness, especially during high workloads. PAQ mapping shows that most competency attributes are in Quadrant A (motivation) and Quadrant D (training), so that improving employee performance needs to be focused on strengthening work motivation, improving work processes and environments, and implementing ongoing training.